Implementation of k-Means Algorithm for Coffee Sales Clustering - Edbert Kevin (Data Science Insights, 2025)
Coffee is one of the most widely consumed beverages worldwide, with a rich history spanning centuries. Coffee is derived from the beans of the Coffea species, primarily Coffea arabica and Coffea canephora (robusta), and is prized not only for its stimulating effects but also for its complex flavor profile. This paper examines the diverse roles of coffee in human culture, its impact on health, and the global coffee industry. Coffee contains bioactive compounds, including caffeine, antioxidants, and diterpenes, which have been studied for their potential health benefits, such as improved cognitive function and reduced risk of certain chronic diseases. However, excessive consumption can lead to negative effects, including sleep disturbances and cardiovascular problems. In addition, the environmental and social impacts of coffee cultivation, including issues related to sustainability, fair trade, and climate change, are critically examined. The paper concludes with a discussion of emerging trends in coffee research, including innovations in processing methods, the rise of specialty coffees, and the growing importance of ethical sourcing in an increasingly globalized market. This comprehensive review emphasizes the need for a balanced understanding of coffee’s benefits and challenges, highlighting its role as a cultural staple and a commodity in the global economy.